60 GHz Propagation Measurement and Modelling: Indoor and Outdoor with Extreme Winter Environments - Satzhan Askarov; Refik Çağlar Kızılırmak; Behrouz Maham; Ikechi Augustine Ukaegbu (Institute of Electrical and Electronics Engineers (IEEE), 2025)
A thorough understanding of how 60 GHz millimeter-wave communication systems behave in severe weather conditions is essential due to the growing use of these technologies in outdoor settings. However, there has been limited research on how snowstorms affect millimeter-wave power propagation, which makes designing and relying on such systems difficult. Motivated by the need to create robust communication solutions for harsh climates, this work investigates the behavior of 60 GHz millimeter-wave power transmission under outdoor snowstorm settings, therefore addressing this gap. The research examines the impact of different transmitter–receiver (T‑R) distances on received power under snowstorm conditions, characterized by an 18 m/s wind speed, 86 % humidity, 0.2 mm/h snowfall rate, 1009.8 mbar atmospheric pressure, and −7 °C temperature, and compares the received power with that in indoor room conditions. Our findings reveal a significant reduction in received power in snowstorm environments compared to indoor settings. Specifically, at T‑R distances of approximately 1 meter, the received power in a snowstorm was observed to be approximately 15 dBm lower than indoors. Furthermore, as the T‑R distance is extended to 7 meters, this contrast is nearly halved, with the outdoor received power registering approximately 7 dBm less than the indoor conditions. These results underscore the considerable influence of snowstorm conditions on 60 GHz millimeter-wave power propagation and emphasize the necessity of comprehending these effects for outdoor communication systems operating in such environments. The study also provides insights into how the path-loss equation can be modified for snowstorm scenarios.
Keywords: Environmental science; Extreme environment; Atmospheric sciences; Remote sensing; Geology; Paleontology; Bacteria; type of access: open access